Development of zero boil-off cooling systems for superconducting self-shielded MEG. Issue 1 (March 2020) - Narasaki, K; Tsunematsu, S
Abstract: A mobile Magneto encephalography (MEG) of Sumitomo Heavy Industries, Ltd. (SHI) uses a high temperature superconducting magnetic shield (HTSMS), Superconductor-Normal-metal-Superconductor (SNS) type Superconducting Quantum Interface Device (SQUID) sensors, and they are cooled by a zero boil-off cooling system. The zero boil-off cooling system consists of a circulating cooled helium gas system for cooling the HTSMS below temperature 90 K and a helium recovery system for cooling the SNS type SQUID sensors to liquid helium temperature. The zero boil-off cooling system are designed to allow measurement in an operating state, allowing arbitrarily long usage. We succeeded first measurement of neuron current in brain by using SHI's MEG with Helium zero-boil off cooling system at April, 2018. This paper describes overview of SHI's MEG, the thermal design of the zero boil-off cooling system for our MEG and the results of cooling tests.